Background rates of erosion and sediment generation in the potomac river basin, USA, derived using in situ 10 Be, meteoric 10 Be, and 9 Be - Portenga,EW; Bierman,PR; Trodick,CD; Greene,SE; DeJong,BD; Rood,DH; Pavich,MJ (Bulletin of the Geological Society of America, 2017)
Beryllium isotopes are often used to estimate rates of landscape change, but results from different beryllium isotope systems have rarely been compared. Here, we combine measurements of in situ and meteoric 10 Be ( 10 Be i and 10 Be m , respectively) with the reactive and mineral phases of 9 Be ( 9 Be reac and 9 Be min , respectively) to elucidate shortand long-term rates of erosion and sediment transport in the Potomac River basin on the North American passive margin. Sixty-two measurements of 10 Be i in alluvium show that the Potomac watershed is eroding on average at 11 m m.y. -1 (~30 Mg km -2 yr -1 ), which is consistent with regional erosion rate estimates. The 10 Be i erosion rates correlate with basin latitude, suggesting that periglacial weathering increased proximal to the Laurentide ice sheet. The average of 55 10 B em / 9 Be reac -derived sediment generation rates (26.2 ± 18.3 Mg km -2 yr -1 ) is indistinguishable from the average of 62 10 Be i rates; however, 10 Be m / 9 Be reac - and 10 Be i -based sediment generation rates are uncorrelated for individual basins. The lack of correlation on a basin-by-basin basis suggests biogeochemical assumptions inherent to the 10 Be m / 9 Be reac technique are not valid everywhere. Contemporary sediment yields (n = 10) are up to 10 times greater than 10 Be i -or 10 Be m -derived sediment generation rates. However, we find that benchmark levels set to manage sediment export into Chesapeake Bay are within the uncertainty of long-term sediment generation rates. Erosion indices derived from 10 Be m measurements range from 0.07 to 1.24, signifying that sediment retention occurs throughout the basin, except in the Appalachian Plateau. Paleo-erosion indices, calculated from the 150 k.y. Hybla Valley sediment core, suggest sediment excavation and storage under colder and warmer climate conditions, respectively.